Silicon Catalyzed C−O Bond Ring Closing Metathesis of Polyethers. (5th October 2022) - Ansmann, Nils; Thorwart, Thaddäus; Greb, Lutz
Abstract: The Lewis superacid bis(perchlorocatecholato)silane catalyzes C−O bond metathesis of alkyl ethers with an efficiency outperforming all earlier reported systems. Chemoselective ring contractions of macrocyclic crown ethers enable substrate‐specific transformations, and an unprecedented ring‐closing metathesis of polyethylene glycols allows polymer‐selective degradation. Quantum chemical computations scrutinize a high Lewis acidity paired with a simultaneous low propensity for polydentate substrate binding as critical for successful catalysis. Based on these mechanistic insights, a second‐generation class of silicon Lewis superacid with enhanced efficacy is identified and demonstrated. Abstract : The Lewis superacid bis(perchlorocatecholato)silane is applied in the selective catalytic C−O ring‐closing metathesis of challenging oligo‐ and polyethers, enabling upcycling of polyethylene glycol. Based on detailed investigations of the reaction mechanism by DFT calculations, an improved second‐generation silicon‐based Lewis superacid is developed.